1985
DOI: 10.1016/s0266-7681(85)80006-1
|View full text |Cite
|
Sign up to set email alerts
|

The Extensor Retinaculum of The Wrist: An Anatomical and Biomechanical Study

Abstract: Through an anatomical and biochemical study, utilizing sixty-five cadaver specimens, the extensor retinaculum of the wrist was examined. It is a complex variable fibrous structure, whose functions are to prevent dorsal bowstringing of the extensor tendons and to prevent radial and ulnar displacement of extensor tendons. We recommend that a portion of the extensor retinaculum be preserved or reconstructed at the time of dorsal wrist surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 3 publications
2
21
1
Order By: Relevance
“…Previous anatomic descriptions have noted the retinaculum to course obliquely and distally from the radial to the ulnar aspect of the wrist, becoming thicker and wider as it passed ulnarward. A second fascial component has also been described coursing distally from ulnar to radial, thus creating a ''fascial V'' (Palmer et al, 1985), but the incidence of this retinacular extension has not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous anatomic descriptions have noted the retinaculum to course obliquely and distally from the radial to the ulnar aspect of the wrist, becoming thicker and wider as it passed ulnarward. A second fascial component has also been described coursing distally from ulnar to radial, thus creating a ''fascial V'' (Palmer et al, 1985), but the incidence of this retinacular extension has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Less attention has been given to anatomic variability surrounding the arrangement of the 5th compartment retinaculum and distal extensions of this retinaculum into the dorsum of the hand (Palmer et al, 1985;Seradge et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,4,5,[8][9][10] However, most previous studies have focused on the soft tissue structures surrounding the ECU tendon, 2,10) which is maintained within a bony groove of the ulna by the retinaculum and subsheath. If the subsheath is torn, stripped, or attenuated, ECU subluxation or dislocation can occur.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a biomechanical study, there will be no increase in bowstringing of the extensor tendons if less than one centimeter of retinaculum is released [19].…”
Section: Discussionmentioning
confidence: 99%